Integrated Aortic-Valve-And-Ascending-Aortic Replacement vs. Partial Replacement in Bicuspid Aortic Valve-Related Aortopathy - Chen, Mi; Xu, Wangli; Ding, Yan; Zhao, Honglei; Wang, Pei; Yang, Bo; Qiao, Huanyu; Zhang, Wei; Zhou, Chenyang; Jia, Junnan; Bai, Tao; Xue, Jinrong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives We sought to evaluate the outcomes of integrated aortic-valve-and-ascending-aortic replacement (IR) versus partial replacement (PR) in patients with BAV-related aortopathy. Methods We compared long-term mortality, reoperation incidence, and the cumulative incidence of stroke, bleeding, significant native valve or prosthetic valve dysfunction, and New York Heart Association (NYHA) functional class II-IV between inverse-probability-weighted cohorts of patients who underwent IR or PR for BAV-related aortopathy in a single center from 2002 through 2019. Patients were stratified into different aortic diameter groups (“Valve Type” vs. “Aorta Type”). Results Among “Valve Type” patients, aortic valve replacement in patients with an aortic diameter > 40mm was associated with significantly higher 10-year mortality than IR compared with diameter 35-40 mm (17.49% vs. 5.28% at 10 years; hazard ratio (HR), 3.22; 95% confidence interval (CI), 1.52 to 6.85; p=0.002). Among patients with “Aorta Type”, ascending aortic replacement in patients with an aortic diameter 52-60 mm was associated with significantly higher 10-year mortality than IR compared with diameter 45-52 mm (14.49% vs. 1.85% at 10 years; HR, 0.04; 95% CI, 1.06 to 85.24; p=0.03). Conclusions The long-term mortality and reoperation benefit that was associated with IR, as compared with PR, minimizing to 40 mm of the aortic diameter among patients with “Valve Type” and minimizing 52 mm of the aortic diameter among those with “Aorta Type”. Trial Registration Treatment to Bicuspid Aortic Valve Related Aortopathy (BAVAo Registry): ChiCTR.org.cn no: ChiCTR2000039867.